The interaction of factors in constructing English learning motivation of China’s government-sponsored overseas academic visiting candidates on an official preparatory program - Chen, Yi (International Journal of English Language, Education and Literature Studies (IJEEL), 2024)
The present study investigates the English learning motivation of China’s government-sponsored overseas academic visiting candidates on an official intensive English preparatory program. A structural equation model (SEM) analysis was conducted on the results of a 33-item questionnaire survey taken by 632 such candidates, most of whom were university academics. By establishing a SEM model for the general sample and four sub-models for its sub-samples, the study delineates the complex interaction of the components in shaping this population’s English learning motivation against the backdrop of China’s grand socio-educational ambition. It also reveals some nuanced differences in the path coefficients in this motivational complex within each of its two sub-sample sets: the candidates with humanities and social science backgrounds vs. those with science backgrounds and the candidates from an institution or program on China’s Double First Class initiative vs. those not. These research findings may help a better understanding of the English learning ecology in today’s China. Theoretically, this study reinforces the usefulness of the prevailing L2 Motivational Self System framework while at the same time accentuating its socio-contextual variance; it also illuminates the future direction pertaining to the application of the Complex Dynamic Systems theory.